Bromatological composition and dry matter production of corn hydroponic fodder - Almeida, Júlio César Silva (2020)
The objective was to evaluate sowing density influence on hydroponic corn fodder bromatological composition, harvested in different ages raised on grass mix substrate. The experimental design used was completely randomized with six replications for each treatment, using 2.0 m² plots (1.0 x 2.0 m). The densities were distributed into factorial array (4x4), consisting in four sowing densities (1.0, 1.5, 2.0 and 2.5 kg m-²) and four cutting ages (10, 15, 20 and 25 days). The dry matter content (DMC) and production (DMP) and crude protein (CP), acid detergent fiber (ADF), Fiber neutral detergent (FND) and ethereal extract (EE) were analyzed each cutting age. In terms of DMP (kg m-²), EE (%) and DMC (kg m-²), it is recommended to use the density 1.0 kg m-² with cutting age of 25 days. Regarding CP (%) the best result was at 15 days of cut and density 2.5 kg m-² and the values for FND (%) and ADF (%) were higher at 25 days at 2.0 kg density 2,0 kg m-². The choice of both best harvesting age and density will depend on what is desired of the nutritional forage (CP, EE, NDF, ADF, DMC and DMP) as well its destination, since very close values were found in all analyzes, regardless of density and age of harvest analyzed.